Mechanochemical assisted extraction as a green approach in preparation of bioactive components extraction from natural products - A review. (November 2022) - Fan, Linhong; Fan, Wenxiang; Mei, Yuqi; Liu, Longchan; Li, Linnan; Wang, Zhengtao; Yang, Li
Abstract: Background: Highly efficient, economic and environment-friendly extraction of target bioactive components from the complex matrices of food supplements or natural medicines has always been a challenge, whether it is for the purposes of bioactivity assay, batch preparation, and more constantly the quality assessment of natural products. Mechanochemical assisted extraction (MCAE), as a green technology, shows distinctive superiority in application of high energy mechanical force acting on the raw materials to dissociate the target components from nature products in aqueous media under normal temperature and without the use of any harmful, dangerous and costly organic solvents. Furthermore, the one pot reaction of MCAE provides a quick process, good reproducibility and a direct transfer of the solution into the instruments like a reverse-phase HPLC system for the subsequent analysis. Scope and approach: This review represents the recent advances in MCAE dealing with the mechanisms, types of equipment, impact parameters, advantages/disadvantages comparing with the other extraction technologies and the application in extraction of food, nutrition and health products derived from natural sources, focusing on samples preparation for the purposes of quality control and physiological & biological activity assay. Key findings and conclusions: Different types of equipment that meet the needs of experiment research and industrial production, and the conditions and impact parameters depending on the diversity of the target compounds to be extracted from the natural raw materials. In one word, MCAE can play a very important role in the sustainable green industrial production of food, nutraceutical and health products. Highlights: An extraction method for natural products that reduces use of organic solvents. Solid auxiliaries are beneficial to the storage and transport during production. Different equipment can meet the different needs of industrial production. One pot reaction provides a quick process and good reproducibility.